Stabilization of the elusive antimony(I) cation and its coordination complexes with transition metals - Kumar, Vikas; Gonnade, Rajesh G.; Yildiz, Cem B.; Majumdar, Moumita (Angewandte Chemie-International Edition, 2021)
Upon stabilization by 5,6-bis(diisopropylphosphino)acenaphthene to form compound 1, the fugitive antimony (I) cation exhibited nucleophilic behavior towards coinage metals. Compound 1 was strategically synthesized at room temperature from SbCl3, the bis(phosphine), and trimethylsilyl trifluoromethanesulfonate taken in a 1:2:3 ratio, whereby the bis(phosphine) plays the dual role of a reductant and a supporting ligand. The generation of 1 involves two-electron oxidation of the ligand to form a P-P bonded diphosphonium dication. Compound 1 was separated from this dication to give both products in pure form in moderate yields. Despite the overall positive charge, the Sb-I site in 1 was found to bind to metal centers, forming complexes with Au-I, Ag-I and Cu-I. Compound 1 reduced Cu-II to Cu-I and formed a coordination complex with the resulting Cu-I species. The effects of the electron-rich bis(phosphine) and the constrained peri geometry in stabilizing and enhancing the nucleophilicity of 1 have been rationalized through computational studies.
Keywords: antimony(I) cation; coordination modes; nucleophilicity; phosphine ligands; reduction